2018
DOI: 10.3758/s13420-018-0355-9
|View full text |Cite
|
Sign up to set email alerts
|

Rapid eye movement density during REM sleep in dogs (Canis familiaris)

Abstract: Dogs (Canis familiaris) are excellent models of human behavior as during domestication they have adapted to the same environment as humans. There have been many comparative studies on dog behavior; however, several easily measurable and analyzable psychophysiological variables that are widely used in humans are still largely unexplored in dogs. One such measure is rapid eye movement density (REMD) during REM sleep. The aim of this study was to test the viability of measuring REMD in dogs and to explore the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
(38 reference statements)
0
9
0
2
Order By: Relevance
“…Even within this group of healthy dogs, we found that age significantly affected the activity pattern across the day, with effects also seen for mass and sex. Recent work has provided insights into sleep architecture in dogs 19,21 , with the development of sophisticated non-invasive polysomnography tools. Surprisingly however, this basic question about sleep-wake cycle in dogs had not been fully characterized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even within this group of healthy dogs, we found that age significantly affected the activity pattern across the day, with effects also seen for mass and sex. Recent work has provided insights into sleep architecture in dogs 19,21 , with the development of sophisticated non-invasive polysomnography tools. Surprisingly however, this basic question about sleep-wake cycle in dogs had not been fully characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Companion dogs offer a distinctive perspective when studying sleep patterns, not only due to shared environmental influences in the home, but also similarities shared by humans and dogs in sleep architecture and sleep-wake cycles 4,[15][16][17][18][19][20] . Both species cycle through phases of wakefulness, drowsiness, rapid eye movement (REM) sleep, and non-rapid eye movement (NREM) sleep 4,15,16,20,21 . As with activity, companion dogs and humans follow a similar circadian rhythm and diurnal sleep pattern 8,21,22 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The electrophysiological recordings were carried out according to the completely non-invasive polysomnography method developed and validated by Kis et al [14] and applied in many studies since (e.g. [15,44,45]). According to the procedure, we recorded the EEG (including electrodes next to the eyes, used as eletrooculogram (EOG); mainly for detecting artefactual muscle movements), electrocardiogram and the respiratory signal of dogs, but only used the EEG signal in these analyses.…”
Section: Electrophysiological Recordingsmentioning
confidence: 99%
“…The previous literature used to estimate priors for each model are shown in Table 1. (Carskadon & Dement, 2005;Yetton et al, 2018) Spindles (Purcell et al, 2016;Warby et al, 2014;Yetton et al, n.d.) Slow Oscillations (Carrier et al, 2011;Massimini, 2004) REM Density (Ficca et al, 1999;Khalsa, Conroy, Duffy, Czeisler, & DIJK, 2002;Kovács, Kosztolányi, & Kis, 2018;Reynolds III et al, 1985;Yetton et al, 2016) Evaluation Criteria…”
Section: Priorsmentioning
confidence: 99%